Lanthanum Oxide Nickel Hydroxide Composite Triangle Nanosheets for Energy Density Asymmetric Supercapacitors - Duan, Huiyu; Shi, Mei; Zhang, Mengfei; Feng, Geyu; Liu, Suli; Chen, Changyun (Frontiers in Chemistry, 2021)
Transition metal hydroxides are a kind of promising electrode materials in electrochemical energy storage but the poor conductivity limits their application. Lanthanides are excellent proton conductors and can usually improve ohter materials‘ intrinsic conductivity. By integrating the merits of lanthanide elements doping and transition metal hydroxide, we designed lanthanum-doped nickel hydroxide (LDNH) with unique ultrathin triangle nanosheet morphology via a controllable synthetic strategy for high performance supercapacitors. When the LDNH used as positive electrode materials in aqueous asymmetric supercapacitor, it reveals an ultrahigh energy density (107.8 W h kg-1 at 800 W kg-1), excellent rate performance (86.9% retention at 4 kW kg-1) and outstanding cycle stability (more than 90% retention after 3000 cycles). This work confirms that via compositing La2O3 and Ni(OH)2 can significantly improve the supercapacitor performance of both pristine La2O3 and transition metal hydroxides. We hope this work would offer a good prospect for developing other lanthanide-doped transition metal hydroxide composites as an attractive class of electrode materials in electrochemical energy storage.